Interpretation and actionability of genetic variants in cardiomyopathies: a position statement from the European Society of Cardiology Council on cardiovascular genomics. (28th January 2022) - Arbustini, Eloisa; Behr, Elijah R; Carrier, Lucie; van Duijn, Cornelia; Evans, Paul; Favalli, Valentina; van der Harst, Pim; Haugaa, Kristina Hermann; Jondeau, Guillaume; Kääb, Stefan; Kaski, Juan Pablo; Kavousi, Maryam; et al.
Abstract: This document describes the contribution of clinical criteria to the interpretation of genetic variants using heritable Mendelian cardiomyopathies as an example. The aim is to assist cardiologists in defining the clinical contribution to a genetic diagnosis and the interpretation of molecular genetic reports. The identification of a genetic variant of unknown or uncertain significance is a limitation of genetic testing, but current guidelines for the interpretation of genetic variants include essential contributions from clinical family screening that can establish a de novo assignment of the variant or its segregation with the phenotype in the family. A partnership between clinicians and patients helps to solve major uncertainties and provides reliable and clinically actionable information. Graphical Abstract: Impact of the cardiologic phenotyping of probands and relatives on ACMG criteria. The ideal 'drawing' of the family pedigree is complete and correct when all available family members have been clinically evaluated and, eventually, longitudinally monitored. *Cardiologists and geneticists may add their own experience, data, and local population information. o Endomyocardial biopsy - anti-GB3 immuno-stain (positive brown; § Typical ultrastructural pattern. DCM = dilated cardiomyopathy; HCM = hypertrophic cardiomyopathy; RCM = restrictive cardiomyopathy; ACM = arrhythmogenic cardiomyopathy; ASD = atrial septal defect; VSD = ventricular septal defect; GB3 = globotriaosylceramide.